1997
DOI: 10.1080/15216549700202361
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the oxidation of 4‐hydroxyanisole catalyzed by tyrosinase

Abstract: Despite the importance of the substrate 4‐hydroxyanisole in melanoma therapy, the kinetics of its oxidation catalyzed by tyrosinase has never been properly characterized. This approach is reported here for the first time. The applicability to 4‐hydroxyanisole of the reaction mechanism of tyrosinase previously proposed for other monophenols has been corroborated. The Michaelis constant for the oxidation of 4‐hydroxyanisole catalyzed by mushroom tyrosinase was (62±1.5jt]μM at pH 7 and increased when the pH decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 9 publications
4
35
0
Order By: Relevance
“…Very recently, the kinetic study of the oxidation of 4HA catalyzed by mushroom PPO has been reported (20). The high catalytic constant of mushroom PPO toward this monophenol was reported in this paper.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Very recently, the kinetic study of the oxidation of 4HA catalyzed by mushroom PPO has been reported (20). The high catalytic constant of mushroom PPO toward this monophenol was reported in this paper.…”
mentioning
confidence: 87%
“…Therefore, this assay method measures half of the steady-state rate. However, when the oxygen consumption is measured then the whole steady-state rate is determined and it is 1.5 times higher than that when the formation of NQH is measured (3O 2 : 2NQH) (15,20,51). NMR assays.…”
Section: Formation and Properties Of The Mbth-quinone Adductsmentioning
confidence: 99%
See 1 more Smart Citation
“…This stoichiometry predicts that V max O 2 /V max ) 1.5 for the monophenolase activity and V max O 2 /V max ) 1 for the diphenolase activity. These ratios were verified experimentally for the oxidation of GHB, L-Tyr, GDHB, and L-DOPA (Table 2) (Rodríguez-López et al, 1992a;Ros et al, 1994a;Espín et al, 1997b).…”
Section: Resultsmentioning
confidence: 91%
“…The determination of these Scheme 1. Sequence of Reactions for the Monophenolase and Diphenolase Activities of Tyrosinase on GHB and GDHB in the Presence of MBTH a a AH + , protonated p-quinoid adduct (tautomery between AH1 and AH2 in an equilibrium shifted toward AH2); A, deprotonated p-quinoid adduct; B, oxidized MBTH-o-quinone adduct after AH + evolution (Espín et al, 1997b). Reactions for monophenolase and diphenolase activities of tyrosinase are detailed in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%